High-Dose Intravenous Ribavirin Therapy for Subacute Sclerosing Panencephalitis - Hosoya, Mitsuaki (American Society for Microbiology, 2001)
Two patients with subacute sclerosing panencephalitis (SSPE) were treated safely and effectively with high doses of intravenous ribavirin combined with intraventricular alpha interferon. The ribavirin concentrations maintained in the serum and cerebrospinal fluid were higher than those which inhibit SSPE virus replication in vitro and in vivo.